Educación, semiología y narrativa (2014)
Approaching language as a fundamental element of communication does not separate systemic relations that exist between the various types of signs. Overall, the communicative universe marks the human being and, of course, leads to build relationships, grasp reality, and try to make others understand it. In the ongoing game of messages are established levels, orderings and rules of life that make those that possess some cognitive experience try to give it to others. The teachers, apprentices, media that carry the same message constitute several systems, among them the educational. The teacher as sender varies his role and sometimes becomes an uninterested teacher, others as a person seeking a job to survive, and others as a researcher that racks in pursuit of new knowledge, or, as a business organizer that conceives the institution as a special institution: a teacher that adapts to contextual, scientific and technological changes, inserted in multiple database, endless information highways, with management and access to information and knowledge in its multiple facets.